Evaluation of Neutralizing Capacity of Tixagevimab plus Cilgavimab (AZD7442) against Different SARS-CoV-2 Variants: A Case Report Study with Comparison to a Vaccinated Population - Constant Gillot; Jean-Louis Bayart; Vincent Maloteau; Jean-Michel Dogné; Jonathan Douxfils; Julien Favresse (Case Reports in Infectious Diseases)
AZD7442 (150 mg of tixagevimab plus 150 mg of cilgavimab) has been approved for the preexposure prophylaxis of COVID-19 and for the treatment of adults and adolescents with COVID-19 who do not require supplemental oxygen and who are at increased risk of severe COVID-19. Thus, the aim of the present study is to evaluate the neutralizing capacity of tixagevimab and cilgavimab across different SARS-CoV-2 variants in two patients who received AZD7442 for immunoprophylaxis. A cohort of subjects (n = 45) who had received the BNT162b2 mRNA COVID-19 vaccine has been included to compare these two preventive strategies. Neutralizing antibody (NAb) titers against several variants were assessed against the wild-type, alpha, beta, gamma, delta, omicron BA.5, and XBB.1.5 variants. Binding antibodies have also been measured. NAbs T1/2 for AZD7442 was 8.1 days (95% CI: 5.1–19.5 days) and was 11.8 days (95% CI: 7.9–23.7 days) for the primo-vaccination cohort. The time to reach neutralization negativity was 108.3 days (95% CI: 66.9–130.7) for AZD7442 compared to 95.4 days (95% CI: 31.0–119.7 days) for the primo-vaccination cohort. The time to reach NAbs’ negativity differs between variants with the maximum value obtained for alpha (i.e., 101.1 days (95% CI: 30.0–135.4 days)) and the minimum obtained for beta (i.e., 61.2 days (95% CI: 37.8–77.1 days)). Our results reinforce the need of reviewing the use of AZD7442 in relation to variants of concern and potentially adapting its administration schedule. AZD7442 could be indicated for short-term prophylaxis in frail patients who may be acutely exposed to SARS-CoV-2.